Powered versus manual toothbrushing for oral health (Review) - Yaacob, Munirah; Worthington, Helen V.; Deacon, Scott A.; Deery, Chris; Walmsley, Damien A.; Robinson, Peter G.; Glenny, Anne-Marie (Wiley-Blackwell, 2014)
Background Removing dental plaque may play a key role maintaining oral health. There is conflicting evidence for the relative merits of manual and powered toothbrushing in achieving this. This is an update of a Cochrane review first published in 2003, and previously updated in 2005. Objectives To compare manual and powered toothbrushes in everyday use, by people of any age, in relation to the removal of plaque, the health of the gingivae, staining and calculus, dependability, adverse effects and cost. Search methods We searched the following electronic databases: the Cochrane Oral Health Group’s Trials Register (to 23 January 2014), the Cochrane Central Register of Controlled Trials (CENTRAL) (The Cochrane Library 2014, Issue 1), MEDLINE via OVID (1946 to 23 January 2014), EMBASE via OVID (1980 to 23 January 2014) and CINAHL via EBSCO (1980 to 23 January 2014). We searched the US National Institutes of Health Trials Register and the WHO Clinical Trials Registry Platform for ongoing trials. No restrictions were placed on the language or date of publication when searching the electronic databases. Selection criteria Randomised controlled trials of at least four weeks of unsupervised powered toothbrushing versus manual toothbrushing for oral health in children and adults. Data collection and analysis We used standard methodological procedures expected by The Cochrane Collaboration. Random-effects models were used provided there were four or more studies included in the meta-analysis, otherwise fixed-effect models were used. Data were classed as short term (one to three months) and long term (greater than three months). Powered versus manual toothbrushing for oral health (Review) 1 Copyright © 2014 The Cochrane Collaboration. Published by John Wiley & Sons, Ltd. ￼ Main results Fifty-six trials met the inclusion criteria; 51 trials involving 4624 participants provided data for meta-analysis. Five trials were at low risk of bias, five at high and 46 at unclear risk of bias. There is moderate quality evidence that powered toothbrushes provide a statistically significant benefit compared with manual tooth- brushes with regard to the reduction of plaque in both the short term (standardised mean difference (SMD) -0.50 (95% confidence interval (CI) -0.70 to -0.31); 40 trials, n = 2871) and long term (SMD -0.47 (95% CI -0.82 to -0.11; 14 trials, n = 978). These results correspond to an 11% reduction in plaque for the Quigley Hein index (Turesky) in the short term and 21% reduction long term. Both meta-analyses showed high levels of heterogeneity (I2 = 83% and 86% respectively) that was not explained by the different powered toothbrush type subgroups. With regard to gingivitis, there is moderate quality evidence that powered toothbrushes again provide a statistically significant benefit when compared with manual toothbrushes both in the short term (SMD -0.43 (95% CI -0.60 to -0.25); 44 trials, n = 3345) and long term (SMD -0.21 (95% CI -0.31 to -0.12); 16 trials, n = 1645). This corresponds to a 6% and 11% reduction in gingivitis for the Löe and Silness index respectively. Both meta-analyses showed high levels of heterogeneity (I2 = 82% and 51% respectively) that was not explained by the different powered toothbrush type subgroups. The number of trials for each type of powered toothbrush varied: side to side (10 trials), counter oscillation (five trials), rotation oscillation (27 trials), circular (two trials), ultrasonic (seven trials), ionic (four trials) and unknown (five trials). The greatest body of evidence was for rotation oscillation brushes which demonstrated a statistically significant reduction in plaque and gingivitis at both time points. Authors’ conclusions Powered toothbrushes reduce plaque and gingivitis more than manual toothbrushing in the short and long term. The clinical importance of these findings remains unclear. Observation of methodological guidelines and greater standardisation of design would benefit both future trials and meta-analyses.